DEVELOPMENT OF LOW-LATENCY WIRELESS COMMUNICATION SYSTEMS FOR AUTONOMOUS VEHICLES - Al – Kahari, Md. Abul Ansar; Jahan, Mst. Israt; Rahman, Md Mohibur (Academic Journal on Science, Technology, Engineering & Mathematics Education, 2024)
This research aims to explore the effectiveness of the L3 protocol in improving the V2X communication systems in key performance areas such as low communication delay, high-speed protocols and the effectiveness under real-life conditions. According to the L3 protocol simulation of the research, which employs platforms including COOJA and NS-3, the latency of the networks is lowered compared to that of the conventional DSRC/LTE system at below one millisecond levels adopting the time slots and the capture effect. These challenges observed on other systems such as delays experienced due to high-speed data transfer are addressed in the protocol. The performed measurements prove that the L3 protocol of the system exhibits reliability and scalability depending on the number of vehicles on the road as well as the network load, and retains its workability even with the number of 225 automobiles. These results conform with prior works that underlined the necessity of using sophisticated and low-latency relative communication systems for the usage of an autonomous vehicle network. In doing so, the study shows a future of L3 protocol in enhancing the current V2X communication systems in aspects of low latency, fast data transfer and competency in various conditions. It is suggested that future research include extensive field trials, the increase of security measures, the analysis of the scalability and integration of the new technologies, and the solution of the interoperability issues for the further investigation of the possibilities of the application of the L3 protocol.